Prevalence, quantitative load and genetic diversity of Campylobacter spp. in dairy cattle herds in Lithuania - Ramonaitė, Sigita (BioMed Central, 2013)
BACKGROUND: Campylobacteriosis is a zoonotic disease, and animals such as poultry, pigs and cattle may act as reservoirs for Campylobacter spp. Cattle shed Campylobacter spp. into the environment and they can act as a reservoir for human infection directly via contact with cattle or their faeces or indirectly by consumption of contaminated food. The aim of this study was to determine the prevalence, the quantitative load and the genetic strain diversity of Campylobacter spp. in dairy cattle of different age groups. RESULTS: Faecal samples of 200 dairy cattle from three farms in the central part of Lithuania were collected and examined for Campylobacter. Cattle herds of all three farms were Campylobacter spp. positive, with a prevalence ranging from 75% (farm I), 77.5% (farm II) to 83.3% (farm III). Overall, the highest prevalence was detected in calves (86.5%) and heifers (86.2%). In contrast, the lowest Campylobacter prevalence was detectable in dairy cows (60.6%). C. jejuni, C. coli, C. lari and C. fetus subsp. fetus were identified in faecal samples of dairy cattle. C. upsaliensis was not detectable in any sample. The high counts of Campylobacter spp. were observed in faecal material of dairy cattle (average 4.5 log(10) cfu/g). The highest numbers of Campylobacter spp. were found in faecal samples from calves (average 5.3 log(10) cfu/g), whereas, faecal samples from cows harboured the lowest number of Campylobacter spp. (average 3.7 log(10) cfu/g). Genotyping by flaA PCR-RFLP analysis of selected C. jejuni isolates showed that some genotypes were present in all farms and all age groups. However, farm or age specific genotypes were also identified. CONCLUSIONS: Future studies are needed to investigate risk factors related to the degree of colonisation in cattle. Based on that, possible measures to reduce the colonisation and subsequent shedding of Campylobacter in cattle could be established. It is important to further investigate the epidemiology of Campylobacter in the cattle population in order to assess associated risks to public health.